Transcriptome and metabolome profiling provide insights into hormone-mediated enhanced growth in autotetraploid seedlings of banana (Musa spp.) - Ni Zhan; Ni Zhan; Li Li; Li Li; Liping Zhang; Weidi He; Qiaosong Yang; Fangcheng Bi; Guiming Deng; Andrew Kiggundu; Ganjun Yi; Ou Sheng (Frontiers in Sustainable Food Systems, 2023)
IntroductionReconstructive breeding based on autotetraploids to generate triploid varieties is a promising breeding strategy in banana (Musa spp.). Therefore understanding the molecular mechanisms underlying the phenotypic differences between the original diploid and its autopolyploid derivatives is of significant importance in such breeding programs of banana.MethodsIn this study, a number of non-chimeric autotetraploid plants, confirmed by flow cytometry and chromosome counting were obtained using colchicine treatment of ‘Pisang Berlin' (AA Group), a diploid banana cultivar highly resistant to Fusarium wilt Tropical Race 4 (Foc TR4) and widely cultivated in Asia.Results and discussionThe autotetraploids showed significant increase in plant height, pseudostem diameter, root length, leaf thickness, leaf area, and leaf chlorophyll content. Transcriptomic analysis indicated that differentially expressed genes were mainly enriched in plant hormone signal transduction, mitogen-activated protein kinase (MAPK) signaling pathway, and carbon fixation in photosynthetic organelles. The genes related to the metabolism, transport or signaling of auxin, abscisic acid (ABA), cytokinin (CTK) and gibberellin (GA), as well as the genes encoding essential enzymes in photosynthetic CO2 fixation were differentially expressed in leaves of autotetraploids and most of them were up-regulated. Metabolomic analysis revealed that the differentially accumulated metabolites were mainly involved in plant hormone signal transduction, porphyrin and chlorophyll metabolism, indole alkaloid biosynthesis, and carbon fixation in photosynthetic organelles. The results therefore, demonstrate that the hormones IAA, ABA, and photosynthetic regulation may play a vital role in the observed enhancement in the autotetraploids. These could be used as molecular and biochemical markers to facilitate the generation of triploid progenies as suitable new varieties for cultivation.